Growth and effect of garlic (Allium sativum) on selected beneficial bacteria - Altuntas,Seda (2019)
Abstract The growing interest of consumers to the new probiotic product has led the industry to focus on it. But viability of probiotic strain has a big challenge during shelf life of food. Therefore, to know the effect of food additives on survival of probiotic is important. The role of probiotics, garlic and yoghurt on the health of humans is widely known. In this study, we focus on finding answers to the question of whether selected beneficial bacteria will survive in the presence of ground garlic solution or fresh garlic juice and obtaining the growth parameters of that strains. Disk diffusion assays revealed that while Bifidobacterium longum BB536 is the most susceptible (49.37 ± 1.07 mm), Lactobacillus acidophilus 74-2 is the most resistant (no inhibition zone) bacteria to the fresh garlic juice, significantly. However, the strains were not adversely affected in possible usage rates of garlic in some Turkish appetizers. Enumeration assays also confirmed these unexpected findings. The addition of certain quantities of ground garlic or fresh garlic juice that did not show antimicrobial activity for selected probiotic strains are suitable for food matrix, especially yogurt based products.